Alteration of Coral Reef Community Structure Caused by Athropogenic Activity in Coastal Area of Giliketapang Island, Probolinggo, East Java, Indonesia - Puspitasari, Lutfiatul; Samino, Setijono; Retnaningdyah, Catur (Journal of Tropical Life Science, 2013)
The aim of this research was to know the effect of anthropogenic activity around the coastal Giliketapang Island to community structure of coral reef. This research used belt transect method which consist of 18 transects in three location (harbour,near the forest and transition areas)at 50-80 m from the coast, with plot size of 2x2m2. Abundance of coral reefs were observed base on the coverage. There are found 11 families of coral reefs. The percentage of coral damage was decrease and the number of species was increase at the far zone from coast. This is also affect the coverage value of coral reefs. Coral coverage at the harbour and near the forest was 53. 06 % and 65. 36 % respectively, whereas in the transition area was 38. 38%. Co-domination between Porites lobata and Chyphastrea microphthalma occurred at the harbour, while Porites mayeri and Acropora spp. co-dominate in near the forest location. Poritidae family dominate in the transition area. Anthropogenic activities at transition location cause severed damage of coral reefs.